The incidence of isolated penile torsion in North India: A study of 5, 018 male neonates. Issue 5 (October 2017) - Bhat, Amilal; Bhat, Mahakshit; Kumar, Vinay; Goyal, Suresh; Bhat, Akshita; Patni, Madhu
Summary: Objective: Congenital penile torsion is a three-dimensional deformity with helical rotation of the distal corporal bodies with the penile crurae remaining fixed to the pubic rami. The first case of congenital penile torsion (hypospadias) was described in 1857. Isolated penile torsion is an under-reported anomaly. The reported incidence of isolated penile torsion is 1.7–27% and severe torsion is 0.7%. There are no studies available from Indian subcontinent on the incidence of isolated penile torque. The objective of this study was to determine the overall incidence of isolated penile torque in a north Indian population. Materials and methods: A prospective study of deliveries of male children was conducted at our institute between April 2014 and June 2015. Penile torsion was measured using a small protractor either by the deviation of the median raphae or the direction of the meatus. Data were collected on the incidence of congenital isolated penile torsion, including the degree and direction (left or right) of torsion. Torsion was classified as mild (<450), moderate (450–900), and severe (>900). Statistical analysis was done using the chi-square test with variables of age and parity of the mother and weight of the child. Results: There were 99 cases of isolated penile torque among 5018 male neonates assessed for penile torque. The incidence of isolated penile torque was 19.7 per 1000 births. The degree of torsion varied from 30 to 110° (average 51.46°). Seventy-nine percent (79%) of them had left side and 21% had right side torque (4:1). The degree of torsion was mild in 30%, with 20% having left side torque and 10% having right side torque (2:1). A moderate degree of torsion was seen in 69%: 84% of them had left torque and only 16% had right sided torque (5:1). Only one patient had severe left torque. The incidence of isolated congenital penile torsion was highest in the maternal age group of >30 years followed by the 26–30-year age group, and was lowest in 21–25 year age group. In multiparous women, the incidence of isolated congenital penile torsion was highest (2.54%), and it was lowest in primiparous women (1.36%). Conclusion: The incidence of isolated penile torsion was 1.97% and the left-to-right ratio was 3:1, but for moderate torque it was 5:1. There was a strong association between incidence of penile torque with the age of the mother ( p  = 0.012) and parity ( p  = 0.008) but not with the weight of the baby ( p  = 0.415). Summary Figure